Comparison of the Clinical Characteristics of Infants with Punctate White Matter Lesions and/or Cystic Lesions - Imai, Ken; Hara, Hiroko; Sawada, Tatsuo; Wada, Masaki (Neuropediatrics, 2022)
Background We aimed to investigate the differences in the clinical characteristics of preterm infants with punctate white matter lesions (PWMLs) and those with cystic periventricular leukomalacia (cPVL) using term-equivalent age magnetic resonance imaging.Methods We conducted a retrospective case–control study to explore the clinical characteristics of infants (< 35 weeks gestation, born between 2007 and 2017 in a single Level III perinatal center) with PWML, cPVL or with PWML plus cPVL and compared them with those of gestational-age-matched controls.Results Among 602 infants, 29, 5, and 4 were assigned to the PWML group, cPVL group, and PWML plus cPVL group (PWML-cPVL group), respectively. Compared to the control group (n = 87), the PWML group had higher birth weights (p = 0.04), rates of histological chorioamnionitis (p = 0.04), vaginal delivery (p = 0.008), and early heart contraction failure (within 72 hours after birth) (p = 0.003). The cPVL group had lower umbilical blood gas base excess (p = 0.01), higher rate of late-onset circulatory collapse (p = 0.008), and higher hydrocortisone requirements (p = 0.03) than the control group (n = 15). The PWML-cPVL group had a higher rate of intraventricular hemorrhage (p = 0.03) than the control group (n = 12). In the multivariate logistic regression analysis, vaginal delivery (odds ratio [OR] = 3.5; 95% confidence interval [CI] = 1.37–9.40; p = 0.009), higher birth weight (per 1 g) (OR = 1.001; 95% CI = 1.0001–1.002; p = 0.03), and early heart contraction failure (OR = 5.4; 95% CI = 1.84–16.8; p = 0.002), were independent risk factors for PWML.Conclusion Clinical characteristics of infants with PWML compared with gestational-age-matched controls differed from those with cPVL or PWML plus cPVL, as PWML were not related to severe disruption of hemodynamics.
Keywords: magnetic resonance imaging; preterm infant; cardiac function; white matter damage